Dosage calculations made incredibly easy!. - Lippincott Williams & Wilkins (Philadelphia : Wolters Kluwer Healt/Lippincott Williams & Wilkins, 2010)
Reviews the basic math needed to perform dosage calculation. It walks readers through the interpretation of hundreds of examples of drug orders and the performance of hundreds of complex dosage calculations.
Fractions -- Decimals and percentages -- Ratios, fractions, proportions, and solving for X -- Dimensional analysis -- Metric system -- Alternative measurement systems -- Drug orders -- Administration records -- Preventing drug errors -- Calculating oral drug dosages -- Calculating topical and rectal drug dosages -- Calculating parenteral injections -- Calculating I.V. infusions -- Calculating pediatric dosages -- Calculating obstetric drug dosages -- Calculating critical care dosages.
Includes bibliographical references (p. 373) and index.
Keywords: Pharmaceutical arithmetic; Pharmaceutical Preparations -- administration & dosage -- Nurses' Instruction; Mathematics -- Nurses' Instruction